2019
DOI: 10.18517/ijaseit.9.6.3560
|View full text |Cite
|
Sign up to set email alerts
|

The Thermal Condition and Comfort Temperature of Traditional Residential Houses Located in Mountainous Tropical Areas: An Adaptive Field Study Approach

Abstract: Thermal comfort may be evaluated from the thermal condition of residential houses and their occupants' satisfaction. This research evaluates the thermal comfort of traditional residential houses located in mountainous areas of Wonosobo, Indonesia. The evaluation is conducted based on the physical condition of residential houses and their occupants' satisfaction factors. A quantitative approach is employed to analyze the theory of static thermal comfort (Predicted Mean Vote/PMV) and that of adaptive thermal com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…On all sides, the average temperature value is between 28.5oC to 31.7oC. The temperature is more than the value of human thermal comfort in the highlands, which is predicted to have a comfortable value of 24oC (Hermawan et al, 2019). The condition of the Wonosobo market in the morning at around 9.00 WIB showed that the conditions were quite hot.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On all sides, the average temperature value is between 28.5oC to 31.7oC. The temperature is more than the value of human thermal comfort in the highlands, which is predicted to have a comfortable value of 24oC (Hermawan et al, 2019). The condition of the Wonosobo market in the morning at around 9.00 WIB showed that the conditions were quite hot.…”
Section: Resultsmentioning
confidence: 99%
“…The comfortable temperature in each region differs according to the microclimatic conditions and the characteristics of the individual. In mountainous areas, it will be different from coastal areas, which have different microclimates (Hermawan et al, 2020). The comfortable temperature may vary for individuals with different activities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to persons, building performance should also be revealed. The connection between temperature and buildings can determine the thermal performance of buildings so that the occupants feel comfortable to stay in the buildings [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…CO2 concentrations cannot be predicted when they reach 1500 ppm. Air temperature and humidity are variables that cannot be separated when discussing thermal comfort, although other factors add to the discussion [9] .…”
Section: Article Infomentioning
confidence: 99%